In Vitro and In Silico Antioxidant Activity of Novel Peptides Prepared from Paeonia Ostii 'Feng Dan' Hydrolysate - Min Wang; Cong Li; Haoyu Li; Zibo Wu; Bang Chen; Yibo Lei; Yehua Shen (MDPI AG, 2019)
Antioxidant peptides derived from natural products have superior performance and broader application prospects. In this study, five novel antioxidant peptides were prepared from Paeonia ostii (P. ostii) seed meal, moreover the bioactive and the relationship between structure and properties of antioxidant peptides were elucidated by quantum chemical calculations. The free radical-scavenging activities were used as indexes to purify and concentrate the antioxidant peptides through five proteases and separation techniques. FSAP (Phe-Ser-Ala-Pro), PVETVR (Pro-Val-Glu-Thr-Val-Arg), QEPLLR (Gln-Glu-Pro-Leu-Leu-Arg), EAAY (Glu-Ala-Ala-Tyr) and VLRPPLS (Val-Leu-Arg-Pro-Pro-Leu-Ser) were identified by nano liquid chromatography−tandem mass spectrometry (LC-MS/MS). In vitro antioxidant activity test, EAAY exhibited the highest 2, 2’-azino-bis (ABTS) and hydroxyl radical-scavenging activity of 98.5% ± 1.1% and 61.9% ± 1.3%, respectively (p < 0.01), at 0.5 mg/mL. In silico calculations were carried out using the density functional theory (DFT) with the B3LYP/6-31G* basis set. According to natural bond orbital (NBO) analysis, the bioactivity of free-radical scavenging of the peptides was presumed. Moreover, the antioxidant peptides demonstrated no obvious cytotoxicity to L929 fibroblast cells. Therefore, the peptides from P. ostii seed by-products might potentially have excellent uses in functional foods, nutraceuticals and pharmacological products.